Tumor-associated macrophages in anti-PD-1/PD-L1 immunotherapy for hepatocellular carcinoma: recent research progress - Li, Ziwei; Duan, Dongyu; Li, Li; Peng, Dan; Ming, Yue; Ni, Rui; Liu, Yao (Frontiers in Pharmacology, 2024)
Hepatocellular carcinoma (HCC) is one of the cancers that seriously threaten human health. Immunotherapy serves as the mainstay of treatment for HCC patients by targeting the programmed cell death protein 1/programmed cell death 1 ligand 1 (PD-1/PD-L1) axis. However, the effectiveness of anti-PD-1/PD-L1 treatment is limited when HCC becomes drug-resistant. Tumor-associated macrophages (TAMs) are an important factor in the negative regulation of PD-1 antibody targeted therapy in the tumor microenvironment (TME). Therefore, as an emerging direction in cancer immunotherapy research for the treatment of HCC, it is crucial to elucidate the correlations and mechanisms between TAMs and PD-1/PD-L1-mediated immune tolerance. This paper summarizes the effects of TAMs on the pathogenesis and progression of HCC and their impact on HCC anti-PD-1/PD-L1 immunotherapy, and further explores current potential therapeutic strategies that target TAMs in HCC, including eliminating TAMs in the TME, inhibiting TAMs recruitment to tumors and functionally repolarizing M2-TAMs (tumor-supportive) to M1-TAMs (antitumor type).